LEGAL VALUE OF THE GRADE «THE INFORMATION PRODUCT» IN THE MODERN INFORMATION LEGISLATION - А. А. Ismanzhanov (Russian Journal of Economics and Law)
In the article the new object of private law - «an information product», specificity of the information legal object, criteria of the many-sided information, which is a subject of an information exchange in the World Wide Web are considered.